ANALISIS HUBUNGAN KINERJA KEUANGAN BERDASAR AKUNTANSI DAN KINERJA KEUANGAN BERDASAR PASAR PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) DENGAN PENGUNGKAPAN CSR SEBAGAI VARIABEL MODERASI - Nanda Putri Angelia; Sinarti Sinarti (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
The objectives of this research are to test and to give empiric evident about influence between financial performance based on accounting which measured by Return On Assets (ROA), Return On Equity (ROE), and Economic Value Added (EVA) and financial performance based on marketplace which measured by stock return. The inconsistency of the result of researches on the influence of financial performance based on accounting to financial performance based on marketplace indicated there is moderate variable that influence the disclosure of Corporate Social Responsibilty (CSR). CSR disclosure is expected to give a signal to external parties including investors in enhancing the corporate image is reflected by increase of stock returns. There are 19 companies that are taken as the sample in this research. The object of this research is companies that listed in Jakarta Islamic Index (JII) from 2008-2013 with 95 data observation. Data are collected by using purposive sampling. Hypotheses in this research are tested using panel data regression and test of absolute difference value. The result of this research showed that financial performance based on accounting which measured by ROA, ROE, and EVA influenced to financial performance based on marketplace which measured by stock return. Meanwhile CSR disclosure in annual company report is not moderating financial performance based on accounting to financial performance based on marketplace.